DEEP LEARNING MELALUI PENDIDIKAN MULTIKULTURAL DALAM BUKU TEKS CERDAS CERGAS BAHASA INDONESIA KELAS XI SMA - Sagala, Naswa Resy Nurhasani Soleha; Yulianti, Uki Hares; Riyanton, Muhammad (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2025)
The educational paradigm shift in Indonesia emphasizes not only academic achievement but also the development of critical, creative, communicative, and collaborative thinking. Deep learning supports this shift by promoting meaningful, mindful, and joyful learning. Indonesian language textbooks, particularly Cerdas Cergas Berbahasa dan Bersastra Indonesia for grade XI, play a strategic role in enhancing language competence while fostering multicultural values aligned with the nation’s diversity. This study applies a qualitative method using the free conversation technique (SBLC) and content analysis of discourse texts, guided by four indicators of multicultural education: tolerance, democracy or freedom, equality, and justice. Findings reveal that the textbook discourse embeds these values and aligns with deep learning principles. Through selected texts, students are encouraged to think critically, interpret socio-cultural contexts, and reflect on their attitudes in daily life. While not every text represents all four values, the presence of local cultural references, regional languages, and elements of national history enriches the material. These features provide contextual learning experiences that go beyond linguistic skills. Consequently, the textbook proves effective in supporting Indonesian language learning that integrates deep learning approaches and strengthens students awareness of multiculturalism.